Structured triage in the emergency department via intelligent assistant service OPTINOFA: Results of a multicenter, cluster-randomized and controlled interventional study in Germany Strukturierte Ersteinschätzung in der Notaufnahme mittels des intelligenten Assistenzdienstes OPTINOFA: Ergebnisse einer multizentrischen, clusterrandomisierten und kontrollierten Interventionsstudie in Deutschland - Blaschke, Sabine; Dormann, Harald; Somasundaram, Rajan; Dodt, Christoph; Graeff, Ingo; Busch, Hans Jörg; Erdmann, Bernadett; Wieckenberg, Marc; Haedicke, Christoph; Esslinger, Katrin; Nyoungui, Elisabeth; Friede, Tim; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2024)
In Germany, a substantial reform of emergency care is strictly recommended. Regulation of patient flows into the ambulatory and stationary sectors remains a major issue. In the OPTINOFA project funded by Innovationsfunds, a new triage system was developed for a structured primary evaluation of both urgency and care level of emergency cases. OPTINOFA was evaluated in a cluster-randomized, controlled multicenter trial using a stepped-wedge design in eight emergency departments (ED) from 1 July 2019 to 31 May 2021. Additionally, data from one ED were used for comparison of temporal changes without intervention. The primary study endpoint represented the increase of patient transfers to the ambulatory sector; secondary endpoints included the outcome, process and quality indicators as well as mean emergency care costs. In the study, 46,558 emergency cases were included in the control period and 37,485 emergency cases in the intervention period. Concerning the primary endpoint, a significant increase of transfers to the ambulatory sector were detected in the per-protocol EDs (p < 0.001, odds ratio = 10.59). Waiting times were significantly reduced by an average 20 min in the intervention phase. Furthermore, a stable admission rate was found within 3 days after initial ED presentation. Cost analysis revealed no increase of treatment expenses within 28 days after ED admission. In this project a valid assistant service for structured primary evaluation of urgency and care level was successfully developed for emergency cases and served as a digital triage instrument with interoperable format. Clinical trial results revealed great potential for the OPTINOFA triage system to control patient flows in emergency and acute medicine.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Clinical emergency and acute medicine; Digital assessment instrument; Emergency department; Intelligent assistant service; Quality indicators; Structured assessment; Triage